Value distribution theory on angular domains for holomorphic mappings and arbitrary families of moving hypersurfaces - Si Duc Quang (Bulletin of Mathematical Sciences, 2023)
Our goal in this paper is to establish some second main theorems for holomorphic mappings from angular domains into projective varieties intersecting arbitrary families of moving hypersurfaces with truncated counting functions. Our results generalize and also improve all previous results for the case of holomorphic mappings from the complex plane.